Monte Carlo variational transition‐state theory study of recombination and desorption of hydrogen on Si(111) - Ibrahim Ali , Noorbatcha (American Institute of Physics (AIP), 1986)
A variational transition‐state theory study of the recombination/desorption rate of H2 from a Si(111) surface using a previously described Monte Carlo procedure [J. Chem. Phys. 8 3, 1389 (1985)] is reported. The potential‐energy surface is expressed as the sum of a lattice potential, a lattice‐adatom interaction term, and an adatom–adatom interaction. Keating’s formulation with the parameters suggested by Weber is used for the lattice potential. The adatom–lattice term is written as a pairwise sum of 60 Morse potentials each multiplied by a hyperbolic switching function that limits each absorption site to one bond. The adatom–adatom interaction is the product of an H2 Morse potential and a switching function that attenuates the H–H interaction as the Si–H bonds form. The parameters of the potential are adjusted to fit the results of hydrogen atom–silicon cluster calculations, the experimental and theoretical results for the H2 insertion barrier into Si and SiH2, and the measured H2(g) bonddissociation energy, fundamental frequency, and equilibrium bond distance. The minimum‐energy path is obtained using a Monte Carlo random walk procedure with importance sampling. The potential surface predicts a 2.52 eV barrier for H2 recombination/desorption and a 0.182 eV barrier to the back reaction. Variational rate calculations are carried out by expressing the dividing surface as a linear combination of the recombination/desorption coordinates and minimizing the computed flux across the surface with respect to the expansion coefficients using a partial grid search. An Arrhenius plot of the minimized flux yields an activation energy and a frequency factor of 2.41 eV and 0.202 cm2 s, respectively. This activation energy is in good agreement with one reported experimental value and is 0.60 eV greater than that found in two other experiments. The frequency factor lies in the middle of the range of the reported experimental values.